Strategi Inovatif Dinas Koperasi Dan UKM Untuk Mendorong Pertumbuhan dan Keberlanjutan UMKM Di Kota Batam - Wijaya, Bagaskara Sagita; Rozi, Feni Fitriani Putri; Caniago, Siti Aminah (Dialektika Publik, 2024)
This study intends to assess the creative techniques used by the Office of Cooperatives and SMEs to promote the expansion and sustainability of SMEs in this context. Case studies and descriptive analysis are the research methods used. Data collection was carried out through interviews with the Office of Cooperatives and SMEs as well as examining documents related to established policies and programs. The study findings show that the Office of Cooperatives and SMEs has implemented a number of cutting-edge methods to help SMEs in the digital era. Developing local e-commerce platforms, providing digital financing, training and educating MSME owners in the use of technology, and promoting and marketing MSMEs using social media and online platforms are just a few of the creative solutions found. The Office of Cooperatives and SMEs is also working with research institutes and banking institutions to create cost-effective technology solutions for MSMEs. The electronic age. To ensure the relevance and sustainability of the applied creative tactics, it is suggested that future research incorporates additional stakeholders, such as MSMEs and educational institutions, in the process of policy making and program implementation.